2016
DOI: 10.3389/fpsyg.2016.01323
|View full text |Cite
|
Sign up to set email alerts
|

Impairments of Social Motor Synchrony Evident in Autism Spectrum Disorder

Abstract: Social interactions typically involve movements of the body that become synchronized over time and both intentional and spontaneous interactional synchrony have been found to be an essential part of successful human interaction. However, our understanding of the importance of temporal dimensions of social motor synchrony in social dysfunction is limited. Here, we used a pendulum coordination paradigm to assess dynamic, process-oriented measures of social motor synchrony in adolescents with and without autism s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
133
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(167 citation statements)
references
References 78 publications
(99 reference statements)
12
133
2
1
Order By: Relevance
“…This disruption in synchronization ability was found both for the imitation and synchrony version of the tasks. This replicate previous research which has found individuals with ASD demonstrate problems in imitation [Charman et al, ; Colombi et al, ; Gallese, ; Oberman & Ramachandran, ; Rizzolatti & Fabbri‐Destro, ; Rogers & Pennington, ; Rogers et al, ; Williams et al, ] as well as other research which has found lower levels of synchronization ability in children and adolescents with ASD [Fitzpatrick et al, ; Marsh et al, ]. Our research makes two important contributions to this literature.…”
Section: Discussionsupporting
confidence: 89%
“…This disruption in synchronization ability was found both for the imitation and synchrony version of the tasks. This replicate previous research which has found individuals with ASD demonstrate problems in imitation [Charman et al, ; Colombi et al, ; Gallese, ; Oberman & Ramachandran, ; Rizzolatti & Fabbri‐Destro, ; Rogers & Pennington, ; Rogers et al, ; Williams et al, ] as well as other research which has found lower levels of synchronization ability in children and adolescents with ASD [Fitzpatrick et al, ; Marsh et al, ]. Our research makes two important contributions to this literature.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, time-series analysis in this context could be extended into the realm of social interaction disorders to search for potential behavioral markers that would help clinicians for a better assessment of patients suffering from a social interaction disorder. Particularly, time-series analysis of the movements has been proved useful for detecting subtle traits like hindered synchronization and patients with ASD when compared to healthy controls (Fitzpatrick et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Finally, this line of research could yield some light into the search of behavioral markers of social interaction impairments by means of time-series analysis (Fitzpatrick et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…So far, the ability to coordinate movements with another person has been mostly studied in persons with ASD using paradigms that are highly rhythmic and therefore not directly related to naturalistic interactions [26,27]. Reduced and more variable IPS between children or adolescents with ASD and an experimenter has mostly been observed with intentional coordination tasks, like a synchronous interpersonal hand-clapping task [28,29], intentional synchronisation of a swinging pendulum [27], synchronised object tapping [29] or in a social motor coordination battery [28].…”
Section: Introductionmentioning
confidence: 99%